Determinant Implementasi Informasi Akuntansi Usaha Kecil Menengah Di Kabupaten Banjarnegara - Alifah Nurfarindha; Heri Yanto (Politeknik Ganesha Medan, 2022)
This study examines the effect of SMEs' perceptions, education level, accounting knowledge, accounting training on the application of accounting information by small and medium enterprises. This study aims to test empirically the effect of perception, education, accounting knowledge and accounting training of SMEs on the application of accounting information. This study uses a quantitative method with purposive sampling technique using the Slovin formula. The data used in this study is primary data obtained from online and offline questionnaires distributed to 104 SMEs throughout Banjarnegara Regency using the purposive sampling method with the slovin formula. From the results of this study, it can be concluded that there is a significant influence between the perception of Small and Medium Enterprises actors and the level of education on the application of accounting information in Small and Medium Enterprises. And there is no significant effect between accounting knowledge and accounting education on the application of accounting information in small and medium enterprises. Suggestions related to the results of this study are: several parties with an interest in improving small and medium enterprises in Banjarnegara Regency, especially the Ministry of Industry, Trade, Cooperatives and Small and Medium Enterprises in Banjarnegara Regency to provide advice and guidelines for the application of accounting information in the operation of a business because accounting information is very necessary in managing a business, do not see that the business is still small or large.